Comparison of efficacy and safety of topical glyceryl trinitrate vs. oral nifedipine in idiopathic perniosis: results of a randomized clinical trial - Khalid, Tanzeela; Maan, Muhammad Arif; Shehzad, Khurram (Journal of Pakistan Association of Dermatologists, 2016)
Objective To compare the therapeutic efficacy and safety of topical vasodilator glyceryl trinitrate (GTN) 0.4% cream, with systemic nifedipine (10-40mg/day) in patients with idiopathic perniosis (IP). Â Methods Patients with IP (n=65) were randomized into group A receiving GTN 0.4% cream (n=31) or group B receiving oral nifedipine, 10-40mg/day (n=34). They were evaluated for improvement in signs and symptoms and any side effects, every 15 days for six weeks. Primary outcome was efficacy and secondary outcome was side effects. Â Results 53 patients completed the study protocol. Twenty-three out of 26 (88%) patients in group A whereas 21 out of 27 (77%) in group B had complete clearance of lesions in six weeks (p=0.52). Clearance of lesions was achieved earlier (10.9 Â±6 days) in group B as compared to (16.6Â±11.5 days) group A (p=0.05). Â Conclusion GTN 0.4% cream is an effective and safe alternative to oral nifedipine in the treatment of IP. Oral nifedipine leads to clearance of lesions earlier than GTN cream. Â